Edukasi Cuci Tangan Pakai Sabun dan Pakai Masker Sebagai Upaya Pengurangan Penyebaran Covid – 19 Pada Masyarakat: Education on Handwashing with Soap and Wearing Masks as an Effort to Reducing the Spread of Covid-19 in the Community - Marthyni Natsir; Nismawati Nismawati (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
Hand washing with soap (CPTS) and wearing a mask are important actions in an effort to reduce the spread of Covid-19. This behavior is not new, but there are still many people who do not understand the importance of implementing CTPS and wearing masks. This community service aims to provide education regarding the 6 steps of CTPS and procedures for using masks correctly in the community, especially in efforts to prevent the transmission of Covid-19. This service was carried out in January 2021 in collaboration with the Indonesian Red Cross (PMI) Gowa Regency. In addition to providing education, this service was given 50 PHBS packages from PMI containing soap and masks. A week after conducting the education, a return visit was made to 50 residents' houses and it was seen that they began to understand the 6 steps of washing hands with soap and the importance of using a mask outside the house